Unstable Osteosynthesis of a Humeral Diaphyseal Fracture as a Cause of a Pseudoarthrosis and an Extensive Bone Defect (A Case Report) - S. V. Bragina; P. V. Iskusov; D. A. Lapidus; A. G. Ivashov; V. G. Kuroptev (Travmatologiâ i Ortopediâ Rossii, 2020)
Relevance. The causes of the formation of a humeral diaphyseal pseudarthrosis can be various risk factors and their combination, including iatrogenic, associated with osteosynthesis technique non-compliance. This leads to instability of the metal constructions with the destructive consequences for the bone tissue and the injured limb function in general. Case presentation. A 60-year-old woman received a right humeral diaphyseal fracture with displacement (АО/АSIF 12-A3) and underwent locking intramedullary osteosynthesis. Subsequently, the fixation failure developed. In 3 years after the primary surgery, a combination of two complications was diagnosed: a nonunion and a defect of the humerus with the formation of a traumatic bone cyst in the distal part. The patient was reoperated: resection of the pseudarthrosis, removal of the right humerus cyst, and revision plate osteosynthesis with bone autografting. A positive result of treatment was obtained: fracture consolidation, reparation of the distal humerus bone structure and restoration of the right upper limb function. Conclusion. The presented clinical case demonstrates the importance of careful preoperative planning of osteosynthesis: the selection of an appropriate implant size, and adequate intraoperative blocking of the intramedullary nail to create a stable “bone-fixator” system. The careful outpatient follow-up of the patient, early detection of possible complications and timely surgical removal of the unstable implant with revision osteosynthesis are required.